THE EFFECTIVENESS OF HOT SEAT GAME ON STUDENTS’ VOCABULARY MASTERY - Dewi, Lusi Oktavia; Sofian, Sofian; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to find out the effectiveness of Hot Seat game in learning vocabulary to the ninth grade students of SMPN 14 Pontianak in academic year 2018/2019. In doing this research, the researcher used pre-experimental study in one group pre-test and post-test design. The sample consisted of 34 students who were chosen by using cluster random sampling. The data had been collected by using measurement technique. Based on the research findings, the mean score of students? pre-test was 48.49 which was considered as ?poor?, while the post-test was 73.98 which was considered as ?average to good?. The tratio (10.53) was bigger than tcritical (2.035) by degree of freedom 33. It meant that the null hypothesis (Ho) was rejected, while alternative hypothesis (Ha) was accepted. The effect size of the treatment was 1.76 which was considered as strong effect size. It can be concluded that Hot Seat game affects significantly the students? vocabulary mastery. The researcher recommends the teacher to use this technique as a variation in teaching process, especially in teaching vocabulary. Keywords: Hot Seat game, Vocabulary mastery